Client assessment on audit firm's quality (CAAF-Q) / PM Dr. Zuraidah Mohd Sanusi … [et al.] - Mohd Sanusi, Zuraidah; Mat Isa, Yusarina; Johari, Razana Juhaida; Ghazali, Aziatul Waznah; Mohamad, Siti Salwa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Public companies are required to have annual external audit investigation which is an unbiased, independent review of a company's business and financial situation conducted by an audit firm. In assessing the audit firm suitability, the firm's management often consider several evaluation criteria that may include objective (e.g. technical capabilities, audit firm size), as well as subjective criteria) e.g. the personality of audit team). However, without past experience the firms ‘management normally select the respective audit firm based on the advice of colleagues within their industry as to decrease some of the risk involved. This practice is subject to criticize as it involves the opinion of the existing audit firm's client. Therefore, the needs for a standard key performance indicators (KPIs) is highly demanded to enable the public organizations to assess and rate the performance of the audit firm. CAAF-Q is aimed to facilitate and provide a guideline on client assessment toward audit firm's quality and convince them in rating and choosing the appropriate audit firm. Besides, this product also offers an avenue for client analysis regarding the quality of audit firm that will enable them in selecting a suitable auditor to audit their company. Practically, CAAF-Q would be useful for all companies that registered under Registrar of Company (ROC) to comply for compulsory audit services.